Pattern of Fatal Firearm Injuries Pertaining to Manner of Death: An Original Research Article - Kaulaskar Shashikant V.1, Kolpe Dayanand V.2, Udaykiran Bhalge3, S K Pandey4, Manoj Pathak5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The purpose of this study was to collect a data related to, but are not limited to, medico legal aspect, manner of death, type of firearm used, anatomical site involved, range of fire and their direction pertaining to manner of death in fatal firearm injury (FFI) cases, as limited data are available for such fatalities in this region. The direction of the internal bullet path has not been investigated in this area. This study was designed to address that deficiency.Method- A prospective study over a period of 22 months was carried out on FFI cases brought to the mortuary.Result –Among 54 FFI cases during study period, homicidal deaths were outnumbered the accidental and suicidal cases. Country made firearm was used in 37.03% FFI cases. More than one entry wound found only in homicidal cases. The typical entry wounds (n-59) in homicide were fired from close or near distance (61.02%), thorax were commonly involved (44.07%) with direction of fire running backward 73.08% (n-19), downward 69.23% (n-18) and towards the right 76.92% (n-20). Entry wound (n-5) in accidental FFI cases were fired from close or near range in 80%, abdomen involved in 80% (n-4) with direction of fire downward 75% (n-3), towards right 75% (n-3) and forward in 50% (n-2),and backward in 50% (n-2). In suicidal cases (n-3) head was involved in 66.67% (n-2) with all direction in backward, upward and towards left side.Conclusions Country made firearms were involved in majority of cases. Multiple shots were present only in homicidal cases. Non contact entry wounds strongly indicate homicidal death. In homicidal death thorax was commonly involved and the direction of internal bullet path was towards the backward, downward and to the right side (B-D-R) in majority of cases. In all suicidal cases, the direction of fire was backward, upward and to left.